Perceptions of Collaboration between Traditional Bone Setters and Formal Care Providers in Cameroon: Bridging Gaps in Injury Care - Arole Darwin Touko; Mark T. Yost; Basile Ngassa; Sithombo Maqungo; Serge Ngekeng; Kudzai Chironga; Aminou Sadjo Salihou; Beme Saouwada Apollinaire; Christelle Maffo; Tonny Orach; Rasheedat Oke; Liza Rosenbloom; et al. (Annals of Global Health, 2026)
Introduction: In Cameroon, there are not enough formal care (FC) providers to treat the high volume of injured patients. Traditional bone setters (TBS) offer widely patronized alternatives for injury treatment; however, the integration of TBS into the healthcare system remains limited. Collaboration between TBS and FC providers could expand the reach and effectiveness of injury care. We explore perceptions of Cameroonian TBS and FC providers regarding injury care and willingness to collaborate. Methodology: We used snowball sampling to survey TBS and FC providers in two regions of Cameroon. Structured questionnaires were used to assess FC and TBS providers’ beliefs regarding potential collaboration. Categorical variables were analyzed with the chi‑squared test while Likert scale responses were analyzed with the Kruskal‑Wallis test. Results: We surveyed 120 providers (n=58 TBS, n=62 FC). TBS providers were significantly older (TBS median age 51, IQR 39‑60 years vs. FC 34, IQR 30‑36 years; P